PEMANFAATAN PEKARANGAN RUMAH PERKOTAAN DENGAN BUDIDAYA SAYURAN HIDROPONIK - Ummu Harmain; Jef Rudiyantho Saragih; Tri Astuti; Muldri P.J. Pasaribu; Pinondang Nainggolan (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
Houses in urban areas generally have limited yard land. With a little creativity, the limited yard land can be used for hydroponic vegetable cultivation. This activity aims to disseminate hydroponic system vegetable cultivation by utilizing limited land for home gardens in urban areas. Activities carried out in the form of counseling, cultivation practices and the manufacture of ab-mix nutrition as well as assistance in hydroponic vegetable cultivation. This activity is able to increase participants' knowledge by producing vegetables for consumption and has the potential to be developed into additional household income